Overdenture retida por implante curto unitário em mandíbulas atróficas: estudo clínico prospectivo - Ala, Lucas Alvarenga Balduino (2019)
Objective: This prospective study aimed to evaluate the effectiveness of the use of a single short implant to retain single implant mandibular overdentures in atrophic mandibles. Material and Methods: Total edentulous individuals who had need to replace or put new complete dentures and who had reduced bone volume in mandibular symphysis region with a maximum height of 15mm for the installation of a short implant without need for bone augmentation procedures were selected. The clinical treatment was divided into three stages: I) protheses preparation; II) implant installation; III) installation of the overdenture system and of overdenture capture. Neodent Titamax Cone Morse implants (Curitiba – Paraná, Brazil) 3.75mm x 7.0mm was used, conventional loading protocol and Equartor CM retention system (Neodent, Curitiba, Paraná, Brazil). At the moment of implant placing, following clinical parameters were collected: implant stability quotient (ISQ), installation torque, bone type and ridge bone type Two outcomes reported by the patient were evaluated before to implant placement and 3 months after overdenture capture: prosthesis satisfaction and oral health impact on quality of life (OHIP-Edent). In addition, maintenance events related to the prosthesis were recorded during the follow-up period. Results: A total of 18 edentulous individuals with a mean age of 65.0 years (±12.1), 14 women (77.8%) were selected. The implant survival rate was 100%. The implant stability quotient (ISQ) increased significantly (p <0.05) after 3 months, from 72.7 (SD = 6.6) to 83.1. The overall OHIP-Edent score reduced in 82.3% and the mean score of patient satisfaction with the mandibular denture increased in 58.5% after 6 months. Conclusion: The use of a single short implant to retain a mandibular overdenture was effective after 6 months of follow up.